IMPLEMENTING ISLAMIC PEDAGOGY THROUGH SELF-DIRECTED LEARNING TO FOSTER STUDENT LEARNING AUTONOMY AT MIS MAMBAUL HIDAYAH - Jamilatun Nafi'ah; Nursyam; Mufida Cholil (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
Islamic pedagogy is an approach based on Islamic values and should be applied in the learning process at Madrasah Ibtidaiyah. In supporting student independence in learning, the application of Islamic pedagogy can be integrated through the Self-Directed Learning model. The purpose of this research is to describe how teachers foster this independence in the practice of Islamic pedagogy. This research uses a qualitative method with a case study approach. The research location is at MIS Mambaul Hidayah Jember. The findings show that the forms of Islamic pedagogy applied by teachers in fostering independent learning include habit-forming activities both outside and inside the classroom. The emphasis on Islamic pedagogy is often found in habitual activities, such as attitudes when praying, performing salat, reading the Qur'an, and habitual manners, which indirectly instil discipline and responsibility in students. Findings in the classroom learning process include the assignment of tasks through worksheets, both in groups and individually. These findings also show that the application of Self-Directed Learning is not yet fully maximised due to obstacles such as differences in students' characteristics in understanding the material and a lack of learning support from parents. This research opens up space for insights into the application of Islamic pedagogy with the integration of the Self-Directed Learning model in Madrasah Ibtidaiyah. Emphasis on SDL model syntax with Islamic pedagogy could be an avenue for future research.